Comparative cytogenetic analysis on four tree frog species (Anura, Hylidae, Hylinae) from Brazil - Kasahara, S.; Silva, APZ; Gruber, S. L.; Haddad, CFB (Karger, 2003)
A comparative cytogenetic analysis was carried out on four Hylinae tree frogs from Brazil (Aparasphenodon brunoi, Corthomantis greeningi, Osteocephalus langsdorffi and Scinax fuscovarius) using Giemsa staining, BrdU replication banding, Ag-NOR staining, C-banding, DAPI and CMA(3) fluorochrome staining, and fluorescence in situ hybridization (FISH) with an rDNA probe. All the species share closely similar 2n = 24 karyotypes, almost indistinguishable by standard staining. The technique of BrdU incorporation allowed the identification of each pair of homologs and the establishment of extensive homeology for the great majority of the chromosomes, mainly of A. brunoi, C greeningi, and O. langsdorffii. Despite highly conserved replication banding patterns, the use of the other banding techniques disclosed some minor differsences, which reinforces the importance of extensive cytogenctic analyses for the karyotypic characterization of Anuran species. The present cytogenctic data confirm the closer proximity of A. brunoi, C greeningi, and O. langsdorfjii, whereas S. fuscovarius is phylogenetically more distant. Copyright (C) 2003 S. Karger AG, Basel